Depressive and anxiety symptoms, and neural correlates of reward and punishment anticipation in female athletes with amenorrhea - Baskaran, Charumathi; Kumar, Poornima; Plessow, Franziska; Nimmala, Supritha; Ackerman, Kathryn E.; Eddy, Kamryn T.; Pizzagalli, Diego A.; Misra, Madhusmita (Frontiers in Endocrinology, 2023)
Objective: Studies in estrogen deficiency states such as primary ovarian insufficiency and Turner syndrome suggest that estrogen status may be an important modulator of mood and emotions. In this study we compared depressive and anxiety symptoms between adolescent and young adult female oligo-amenorrheic athletes (AA) and eumenorrheic females (EM), and explored structural, and functional changes in related brain areas during reward processing, a behavioral construct that is altered in depression and anxiety. Methods: We included (i) 24 AA participating in ≥4 hours/week of aerobic exercise or running ≥20 miles/week for ≥6 months in the preceding year, with lack of menstrual cycles for ≥3 months within at least 6 preceding months of oligo-amenorrhea, OR in premenarchal girls, absence of menses at >15 years), and (ii) 27 EM aged 14-25 years. Participants completed the Beck Depression Inventory-II (BDI-II), State and Trait Anxiety Inventory (STAI), and Mood and Anxiety Symptoms Questionnaire (MASQ). Structural MRI and brain activation during a functional MRI (fMRI) task that probes reward and punishment processing was examined in a subset of 10 AA and 23 EM. Results: Mean age and BMI of AA and EM groups were 20.8±0.5 vs. 21.1±0.5 years, p=0.6 and 20.2±0.3 vs. 21.8±0.4 kg/m2, p=0.005, respectively. While groups did not differ for BDI-II scores, AA had higher anhedonic depression MASQ scores (p=0.04), and STAI (p=0.03) scores vs. EM. In the fMRI subset, AA had higher caudate volumes vs. EM [F(1, 29)=9.930, p=0.004]. Lower activation observed in the right caudate during reward anticipation in AA compared with EM (p=0.036) suggests blunted reward processing in the striatum in estrogen deficient states. Conclusion: Athletes with amenorrhea had higher depressive and anxiety symptomatology compared to eumenorrheic young women. Exploratory analyses demonstrated increased caudate volumes and decreased caudate activation during reward processing in athletes with amenorrhea suggesting that estrogen may play a role in reward processing.